Preparation method of bf-C-dots / GN composite material and glucose electrochemical sensor

By using bf-C-dots/GN composite materials, the existing non-enzymatic glucose electrochemical sensors have been solved, and high selectivity detection and rapid and effective detection effects of glucose are achieved.

CN119528129APending Publication Date: 2025-02-28JIANGSU COLLEGE OF INFORMATION TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411689187.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Existing non-enzymatic glucose electrochemical sensors have problems such as insufficient stability, poor anti-interference and low selectivity, which limits their application in diabetes diagnosis and monitoring.

Method used

Using bf-C-dots/GN composite material, the binding affinity and selectivity of the material for glucose is improved by integrating multiple boric acid groups into one and combining with the carbon material graphene, and glucose is detected by electrochemical means.

Benefits of technology

High selective detection of glucose is achieved, with a wide linear detection range (1.0×10-5–7.0×10-5M), a low detection limit (1.14×10-6M) and good stability, and can quickly and effectively detect glucose in human serum.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119528129A_ABST
    Figure CN119528129A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a bf-C-dots / GN composite material and a glucose electrochemical sensor, and the preparation method of the bf-C-dots / GN composite material comprises the following steps: dissolving phenylboronic acid in ultrapure water, adding NaOH under continuous stirring to adjust the pH value of the phenylboronic acid solution to 9.0, then blowing by nitrogen to remove O2 dissolved in the solution, and carrying out vacuum drying to obtain the bf-C-dots / GN composite material. Then transferring the solution to a high-pressure reaction kettle, heating to 160 DEG C, continuing for 10 hours, cooling the solution containing the boric acid functionalized carbon dots to room temperature after the reaction is finished, centrifuging for 30 minutes at the rotating speed of 10000 rpm, and taking supernatant liquid to obtain a bf-C-dots material; the preparation method comprises the following steps: ultrasonically dispersing graphene oxide in double distilled water to form a uniform solution, uniformly mixing a graphene oxide solution and a bf-C-dots solution, transferring the mixture to a high-pressure reaction kettle, heating to 90 DEG C, continuing for 4 hours, cooling to room temperature, and centrifuging at the rotating speed of 10000 rpm for 10 minutes to obtain the bf-C-dots / GN composite material. The anti-interference performance is good; and the sensitivity is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of non-enzymatic glucose electrochemical sensor technology, specifically to a bf-C-dots / GN composite material and a method for preparing a glucose electrochemical sensor. Background Technology

[0002] Glucose is an essential substance for life activities and is widely distributed in the blood of living organisms. Blood glucose levels are a crucial diagnostic parameter for many metabolic disorders, such as diabetes. Normal fasting blood glucose in the human body is less than 5.0 mmol / L; when fasting blood glucose exceeds 7.0 mmol / L and clinical symptoms are present, diabetes can be diagnosed. Accurate and reliable blood glucose data are undoubtedly vital in the diagnosis, treatment, and prognosis management of diabetes. Furthermore, blood glucose is an important physiological indicator for athletes during sports training. Reasonable blood glucose monitoring and adjustment can help athletes better control their blood glucose levels, improve training effectiveness, and reduce the occurrence of adverse events such as sports injuries and hypoglycemia. Therefore, close monitoring of glucose concentration is of great significance in clinical diagnosis, biotechnology, the food industry, and competitive sports.

[0003] To date, various methods for glucose detection have been developed, such as glucose oxidase methods, spectroscopic methods, and chromatographic methods. These methods all suffer from drawbacks such as instrument limitations, the need for specialized technical personnel, and high costs. Electrochemical methods have achieved significant advantages in terms of sensitivity, low cost, and high efficiency in glucose quantification. Glucose electrochemical sensors are mainly divided into two categories: enzyme-based glucose sensors and non-enzyme-based glucose sensors. Enzyme-based sensors typically exhibit high sensitivity and excellent selectivity, but their biggest problem is the inherent instability caused by the enzyme's properties, thus limiting the practical application of enzyme-based sensors. In contrast, non-enzyme-based glucose sensors offer better stability and simplicity. Most research focuses on using various metallic materials, such as noble metals, metal alloys, and metal oxides, to construct non-enzyme-based glucose sensors exhibiting direct electrocatalytic performance. However, these metal-based methods still have some drawbacks. First, metal-based sensors are susceptible to surface contamination due to the accumulation of adsorption intermediates. Second, the high cost of metallic materials limits their commercial application. Finally, metal-based sensors exhibit poor selectivity for glucose. Summary of the Invention

[0004] The purpose of this section is to outline some aspects of the embodiments of the present invention and to briefly describe some preferred embodiments. Simplifications or omissions may be made in this section, as well as in the abstract and title of this application, to avoid obscuring the purpose of these documents; however, such simplifications or omissions should not be construed as limiting the scope of the invention.

[0005] Therefore, the purpose of this invention is to provide a method for preparing a bf-C-dots / GN composite material and a glucose electrochemical sensor, which has a wide linear detection range for glucose, good anti-interference ability and high sensitivity.

[0006] To address the aforementioned technical problems, according to one aspect of the present invention, the present invention provides the following technical solution:

[0007] A method for preparing a bf-C-dots / GN composite material, the specific steps of which are as follows:

[0008] S1. Dissolve 0.2g of phenylboronic acid in 20mL of ultrapure water. Add 0.1M NaOH while stirring continuously to adjust the pH of the phenylboronic acid solution to 9.0. Then, remove dissolved O2 from the solution by blowing with nitrogen gas.

[0009] S2. The above solution was then transferred to a high-pressure reactor, heated to 160°C and maintained for 10 hours. After the reaction was completed, the solution containing boric acid functionalized carbon dots was cooled to room temperature and centrifuged at 10,000 rpm for 30 minutes to remove large particulate precipitates and obtain bf-C-dots material.

[0010] S3. Graphene oxide was ultrasonically dispersed in double-distilled water to form a concentration of 1 mg / mL. -1 A homogeneous solution;

[0011] S4, add 1 mL of 1 mg mL -1 The graphene oxide solution and 10 mL of bf-C-dots solution were mixed evenly, transferred to a high-pressure reactor, heated to 90°C and maintained for 4 h, cooled to room temperature and centrifuged at 10000 rpm for 10 min to obtain the bf-C-dots / GN composite material.

[0012] In a preferred embodiment of the preparation method of the bf-C-dots / GN composite material described in this invention, in step S2, after removing large particulate precipitates, the solution is dialyzed in a dialysis bag for 24 hours to further purify the bf-C-dots material.

[0013] In a preferred embodiment of the preparation method of the bf-C-dots / GN composite material described in this invention, the graphene oxide is synthesized from natural graphite powder using a modified Hummers method.

[0014] In a preferred embodiment of the preparation method of the bf-C-dots / GN composite material described in this invention, the high-pressure reactor has a polytetrafluoroethylene lining.

[0015] A method for preparing a glucose electrochemical sensor, the specific steps of which are as follows:

[0016] S1. First, the glassy carbon electrode was polished to a bright finish using 1μM, 0.3μM and 0.05μM Al2O3 powders, respectively, and then ultrasonically cleaned until the redox potential difference measured by cyclic voltammetry was less than 80mV.

[0017] S2. Then, the electrode surface was dried with a nitrogen stream. Then, 7.5 μL of bf-C-dots / GN aqueous solution was pipetted onto the polished glassy carbon electrode surface and dried in an oven for 5-8 min.

[0018] S3. Using the glassy carbon electrode modified with the prepared composite material bf-C-dots / GN as the working electrode, the saturated calomel electrode as the reference electrode, the platinum electrode as the counter electrode, and potassium ferrocyanide as the electrochemical probe, a glucose electrochemical sensor was obtained.

[0019] In a preferred embodiment of the method for preparing a glucose electrochemical sensor according to the present invention, in step S1, the glassy carbon electrode is polished on deer hide until it is shiny.

[0020] In a preferred embodiment of the method for preparing a glucose electrochemical sensor according to the present invention, in step S1, the glassy carbon electrode is ultrasonically cleaned sequentially using 1:1 nitric acid, ethanol and double-distilled water.

[0021] In a preferred embodiment of the preparation method of the glucose electrochemical sensor described in this invention, the drying temperature of the oven is 60°C.

[0022] Compared with the prior art, the beneficial effects of the present invention are:

[0023] 1. Since boric acid and its derivatives can reversibly and efficiently covalently bind with diols to form cyclic boric acid esters, which can be used as molecular probes for biosensors to identify carbohydrate compounds, this invention integrates multiple boric acid groups into one to improve the binding affinity and selectivity of boric acid-based nanomaterials for glucose, and combines them with carbon material graphene (GN) to improve electron transport capability, thus enabling the construction of a highly selective non-enzymatic glucose electrochemical sensor.

[0024] 2. A composite material was prepared using a simple and environmentally friendly synthesis method, and glucose was detected using electrochemical methods. The linear range of the prepared sensor's response to glucose was 1.0 × 10⁻⁶. -5 –7.0×10 -5 M, detection limit is 1.14 × 10 -6 M has excellent specificity and good stability, and can quickly and effectively detect glucose in human serum. Attached Figure Description

[0025] To more clearly illustrate the technical solutions of the embodiments of the present invention, the present invention will be described in detail below with reference to the accompanying drawings and detailed embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort. Wherein:

[0026] Figure 1 (A) The scan rates (10, 30, 50, 80, 110, 140, 170, 200, 230, 260, 290, 320, 350, 380, 410, 440, 470, 500 mV s) of bf-C-dots / GN / GCE in 5 mM K₄Fe(CN)₆ and 0.1 M PBS (pH 8.0) solutions are shown in Figure 1. -1 The cyclic voltammetry diagram of ) Figure 1 (B) is a graph showing the linear relationship between the anode peak current and the cathode peak current and the square root of the sweep rate;

[0027] Figure 2 Differential pulse voltammetry in 5 mM K4Fe(CN)6 and 0.1 M PBS (pH 8.0) solutions before and after recognition of bf-C-dots / GN / GCE with glucose;

[0028] Figure 3 (A) A series of differential pulse voltammetric curves of bf-C-dots / GN / GCE with different glucose concentrations in 0.1M PBS (pH 8.0) containing 5mM K4Fe(CN)6. Figure 3 (B) is a graph showing the linear relationship between bf-C-dots / GN / GCE current and glucose concentration;

[0029] Figure 4 The figure shows the current response of bf-C-dots / GN / GCE to different substances, where glucose is glucose; uric acid is uric acid; dopamine is dopamine; H2O2 is hydrogen peroxide; ascorbic acid is ascorbic acid; L-tryptophan is L-tryptophan; and Ca2+ is calcium. 2+ It is calcium ions. Detailed Implementation

[0030] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings.

[0031] Secondly, the present invention is described in detail with reference to the schematic diagrams. When detailing the embodiments of the present invention, for ease of explanation, the cross-sectional views illustrating the device structure may be partially enlarged, not according to the usual scale. Furthermore, the schematic diagrams are merely examples and should not limit the scope of protection of the present invention. In addition, actual fabrication should include three-dimensional spatial dimensions of length, width, and depth.

[0032] To make the objectives, technical solutions and advantages of the present invention more clear, the embodiments of the present invention will be described in further detail below with reference to the accompanying drawings.

[0033] This invention provides a method for preparing a bf-C-dots / GN composite material and a glucose electrochemical sensor, which has a wide linear detection range for glucose, good anti-interference ability and high sensitivity.

[0034] Example 1

[0035] Boric acid possesses advantages such as low cost, good stability, and easy reversible regeneration. Boric acid and its derivatives can reversibly and efficiently covalently bind with diols to form cyclic boronic acid esters, which can be used as molecular probes for biosensors to identify carbohydrate compounds. By integrating multiple boronic acid groups, the binding affinity and selectivity of boronic acid-based nanomaterials for glucose can be improved. Combining them with carbon material graphene (GN) enhances electron transport capabilities, enabling the construction of highly selective non-enzymatic glucose electrochemical sensors.

[0036] The specific preparation method of bf-C-dots / GN composite material is as follows:

[0037] S1. Dissolve 0.2g of phenylboronic acid in 20mL of ultrapure water. Add 0.1M NaOH while stirring continuously to adjust the pH of the phenylboronic acid solution to 9.0. Then, remove dissolved O2 from the solution by blowing with nitrogen gas.

[0038] S2. The above solution was then transferred to a high-pressure reactor with a polytetrafluoroethylene lining, heated to 160°C and held for 10 hours. After the reaction was completed, the solution containing boric acid functionalized carbon dots (bf-C-dots) was cooled to room temperature and centrifuged at 10,000 rpm for 30 minutes to remove large particles of precipitate and obtain bf-C-dots material.

[0039] S3. Using natural graphite powder as raw material, graphene oxide (GO) was synthesized using a modified Hummers method. The graphene oxide was ultrasonically dispersed in double-distilled water to form a concentration of 1 mg / mL. -1 A homogeneous solution;

[0040] S4, add 1 mL of 1 mg mL -1The graphene oxide solution and 10 mL of bf-C-dots solution were mixed evenly, transferred to a high-pressure reactor, heated to 90°C and maintained for 4 h, cooled to room temperature and centrifuged at 10000 rpm for 10 min to obtain the bf-C-dots / GN composite material.

[0041] Example 2

[0042] A glucose electrochemical sensor can be fabricated by obtaining the bf-C-dots / GN composite material. The specific fabrication process of the glucose electrochemical sensor is as follows:

[0043] S1. First, the glassy carbon electrode (GCE) was polished on deerskin until it was shiny with 1μM, 0.3μM and 0.05μM Al2O3 powder respectively. Then, it was ultrasonically cleaned with 1:1 nitric acid, ethanol and double-distilled water in sequence until the redox potential difference measured by cyclic voltammetry was less than 80mV.

[0044] S2. Then, the electrode surface was dried with a nitrogen stream. Then, 7.5 μL of bf-C-dots / GN aqueous solution was pipetted onto the polished glassy carbon electrode surface and dried in an oven at 60°C for 5-8 minutes.

[0045] S3. Using the glassy carbon electrode modified with the prepared composite material bf-C-dots / GN as the working electrode, the saturated calomel electrode as the reference electrode, the platinum electrode as the counter electrode, and potassium ferrocyanide as the electrochemical probe, a glucose electrochemical sensor was obtained.

[0046] To verify the performance and indicators of the glucose electrochemical sensor prepared in this invention, its electrochemical performance was investigated by electrochemical detection of glucose under different conditions using a three-electrode system in phosphate buffer solution.

[0047] Figure 1 The dynamics of the bf-C-dots / GN electrode interface were studied using cyclic voltammetry, such as... Figure 1 (A) and Figure 1 As shown in (B), with the increase of the scan rate, the peak potentials of the cathode and anode shift in opposite directions. Furthermore, the peak currents (I) of both the cathode and anode gradually increase, and these peak currents range from 10 to 500 mM / s. -1 Within the range of scan rate (v) 1 / 2 The square root of I and v changes linearly during oxidation and reduction processes. 1 / 2 The equations are expressed as follows: I pa (μA)=8.337+5.793v 1 / 2 (mVs -1 R = 0.9982, I pc (μA)=-16.37-5.250v1 / 2 (mVs -1 R = 0.9951. The results indicate that the redox reaction is mainly dominated by diffusion-controlled electrochemical processes.

[0048] Figure 2 The recognition ability of bf-C-dots / GN / GCE (glucose electrochemical sensor) for glucose was demonstrated in 5 mM K4Fe(CN)6 and 0.1 M PBS (pH 8.0) solutions. The differential pulse voltammograms of bf-C-dots / GN / GCE in 5 mM K4Fe(CN)6 and 0.1 M PBS (pH 8.0) solutions showed a high anodic peak current. With the addition of glucose, the current intensity of bf-C-dots / GN / GCE decreased significantly. This is because glucose effectively binds to the borate groups on the electrode surface, making it difficult for the electrochemical probe K4Fe(CN)6 in solution to transfer to the electrode surface. This indicates that the material has good recognition performance for glucose and can be used as a material for constructing glucose electrochemical sensors.

[0049] Figure 3 To investigate the detection range of the sensor, the differential pulse voltammetry method was used. For example... Figure 3 (A) and Figure 3 (B) It can be seen that the peak current gradually decreases with increasing glucose concentration. This is because the negatively charged electrochemical probe (Fe(CN)6) 4- The electrostatic repulsion between OH- and negatively charged bf-C-dots / GN originates from the electrostatic repulsion of OH- under alkaline conditions. - Anions are added to boron atoms. Furthermore, a slight negative shift in the anodic peak potential was observed, a phenomenon attributed to complexation. Within the range of 0.01–7 mM, the peak current exhibited a linear relationship with glucose concentration, with a correlation coefficient of 0.9946 and a regression equation of logI(μA) = 0.7124 + 0.3893logc(mM). The detection limit was calculated to be 1.14 μM.

[0050] Figure 4 The anti-interference performance of the sensor was tested. The graph shows that the peak current of bf-C-dots / GN / GCE decreased significantly after the addition of glucose. Subsequent addition of other interfering substances did not result in significant changes in the current response. This indicates that the sensor's anti-interference performance is affected by uric acid, dopamine, hydrogen peroxide, ascorbic acid, L-tryptophan, and Ca2+. 2+ In the coexisting system, the composite electrode exhibits good selectivity for glucose, and also for uric acid, dopamine, hydrogen peroxide, ascorbic acid, L-tryptophan, and calcium. 2+ It has good anti-interference performance.

[0051] Although the present invention has been described above with reference to embodiments, various modifications can be made and components can be replaced with equivalents without departing from the scope of the invention. In particular, as long as there is no structural conflict, the features in the disclosed embodiments can be combined with each other in any manner. The lack of an exhaustive description of these combinations in this specification is merely for the sake of brevity and resource conservation. Therefore, the present invention is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.

Claims

1. A method for preparing a bf-C-dots / GN composite material, characterized in that: The specific steps are as follows: S1. Dissolve 0.2 g of phenylboric acid in 20 mL of ultrapure water, add 0.1 M NaOH under constant stirring to adjust the pH of the phenylboric acid solution to 9.0, and then blow nitrogen gas to remove dissolved O2 in the solution; S2, then transferring the above solution to a high-pressure reactor, heating it to 160°C for 10 hours, and after the reaction is completed, cooling the solution containing the boric acid functionalized carbon dots to room temperature, and centrifuging it at a speed of 10000 rpm for 30 minutes to remove large particle precipitates, thereby obtaining bf-C-dots material; S3. Ultrasonic dispersion of graphene oxide in double distilled water to form a concentration of 1 mg mL -1 A homogeneous solution; S4, 1mL of 1mg mL -1 The graphene oxide solution and 10 mL of bf-C-dots solution were mixed evenly, transferred to a high-pressure reactor, heated to 90 °C for 4 h, cooled to room temperature and centrifuged at 10000 rpm for 10 min to obtain a bf-C-dots / GN composite material.

2. The method for preparing a bf-C-dots / GN composite material according to claim 1, characterized in that: In step S2, after removing the large particle precipitate, the solution was dialyzed in a dialysis bag for 24 h to further purify the bf-C-dots material.

3. The method for preparing a bf-C-dots / GN composite material according to claim 1, characterized in that: The graphene oxide is synthesized from natural graphite powder as a raw material by adopting an improved Hummers method.

4. The method for preparing a bf-C-dots / GN composite material according to claim 1, characterized in that: The autoclave had a polytetrafluoroethylene lining.

5. A method for preparing a glucose electrochemical sensor, characterized in that: The specific steps are as follows: S1. First, the glassy carbon electrode was polished to a bright finish with 1 μM, 0.3 μM, and 0.05 μM A12O3 powders, respectively, and then ultrasonically cleaned until the redox potential difference measured by cyclic voltammetry was less than 80 mV. S2, then blow dry the electrode surface with a nitrogen stream, then use a pipette to transfer 7.5 μL of the bf-C-dots / GN aqueous solution prepared as claimed in any one of claims 1 to 4 and drop-coat it on the polished glassy carbon electrode surface, and dry it in an oven for 5-8 minutes; S3. Use the prepared composite material bf-C-dots / GN modified glassy carbon electrode as the working electrode, the saturated calomel electrode as the reference electrode, the platinum electrode as the counter electrode, and potassium ferrocyanide as the electrochemical probe to obtain a glucose electrochemical sensor.

6. The method for preparing a glucose electrochemical sensor according to claim 5, characterized in that: In step S1, the glassy carbon electrode is polished on the deerskin until it is shiny.

7. The method for preparing a glucose electrochemical sensor according to claim 5, characterized in that: In step S1, the glassy carbon electrode is ultrasonically cleaned using 1:1 nitric acid, ethanol and double distilled water in sequence.

8. The method for preparing a glucose electrochemical sensor according to claim 5, characterized in that: The drying temperature of the oven was 60°C.

Citation Information

Patent Citations

  • Preparation method of double-enzyme glucose sensor based on graphene

    CN103033549A

  • Boric acid-functionalized fluorescent nanomaterial, and application thereof in glucose detection

    CN109852373A

  • Detection method of polyhydroxy compound

    CN113916845A

  • Glucose-derived carbon nanosphere electrochemical sensor, preparation method and application thereof

    CN114002291A

  • Electrode and method for detecting analyte using same

    WO2015152520A1